3D printing : understanding additive manufacturing - Gebhardt, Andreas; Kessler, Julia; Thurn, Laura (Hanser Publishers, 2019)
"This book is a clear and concise guide to Additive Manufacturing (AM), now a well-established valuable tool for making models and prototypes, and also a manufacturing method for molds and final parts finding applications in industries such as medicine, car manufacturing, and aerospace engineering. The book was designed as a supporting material for special courses on advanced manufacturing technology, and for supplementing the content of traditional manufacturing lessons. This second edition has been updated to account for the recent explosion of availability of small, inexpensive 3D printers for domestic use, as well as new industrial printers for series production that have come onto the market. Contents: - Basics of 3D Printing Technology - Additive Manufacturing Processes/3D Printing - The Additive Manufacturing Process Chain and Machines for Additive Manufacturing - Applications of Additive Manufacturing - Perspectives and Strategies of Additive Manufacturing - Materials and Design - Glossary of Terms, Abbreviations, and Definitions"--